Coincidental or Connected: Synchronous Giant Gastric GIST and Malignant Colonic Polyp: A Case Report - Terukumar Chandrasekaran; Lim Li Yi; JJ Mah; RK Sriram; Nik Amin Sahid (Gazi Medical Journal)
Gastrointestinal stromal tumors (GIST) are rare mesenchymal neoplasms of the gastrointestinal tract, most commonly occurring in the stomach. The concurrence of GIST with another malignancy is an uncommon phenomenon, with few works of literature reported. We report a rare synchronous giant gastric GIST with a malignant colonic polyp. A 70-year-old woman presented with an upper abdominal mass. There were no changes in bowel habits. CEA level was normal. Contrasted computed tomography of the abdomen revealed a huge gastric mass with incidental findings of a suspicious mass in the sigmoid colon. Esophagogastroduodenoscopy revealed extrinsic compression with normal overlying mucosa, suggesting a submucosal mass. Colonoscopy revealed a large polypoidal mass in the sigmoid colon, and initial biopsy revealed tubulovillous adenoma with high-grade dysplasia. Wide local excision of the gastric tumor and table snare polypectomy were performed. The base of the polyp was also taken for biopsy. The patient had an uneventful recovery and was discharged home well. Postoperative histopathological examination showed gastric GIST and adenocarcinoma of the sigmoid polyp. The polyp base showed no malignancy. The patient was started on imatinib 400 mg once a day. GIST and colon malignant polyps are two distinct types of neoplasms that can occur synchronously. GIST tumours arise from the interstitial cells of Cajal and are characterized by mutations in KIT/PDGFRA genes. Conversely, malignant polyps are epithelial tumours that arise from the colonic mucosa classically because of alterations in the APC tumour suppressor gene, resulting in overactivation of the Wnt/β-catenin signaling pathway. Synchronous GISTs and malignant colon polyps are rare, and their molecular basis is distinct. However, it is crucial to consider the possibility of genetic predisposition in patients with such tumors. In a case of GIST, the surgeon should recognize the possibility of another tumor with a different histological origin. High clinical analysis needed during laparotomy for GIST to detect a synchronous tumor. Due to its rare occurrence and limited literature further GIST with another synchronous tumor must be conducted to help surgeons optimize patient management.